Rab11a Regulates the Development of Cilia and Establishment of Planar Cell Polarity in Mammalian Vestibular Hair Cells - Chen, Bin-Jun; Qian, Xiao-qing; Yang, Xiao-yu; Jiang, Tao; Wang, Yan-mei; Lyu, Ji-han; Chi, Fang-lu; Chen, Ping; Ren, Dong-dong (Frontiers in Molecular Neuroscience, 2021)
Vestibular organs have unique planar cell polarity, and their normal development and function are dependent on the regular polarity of cilia. requires. Rab11a is a small G protein that participates in the transportation of intracellular and extracellular materials for polarity formation; however, our understanding of the mechanisms of the actions of Rab11a in vestibular organs is limited. Here, we showed that the general shape of the utricle was abnormal in Rab11aCKO/CKO mice. These mice also showed abnormal morphology of the stereocilia bundles, which were reduced in both length and number, as well as disturbed tissue-level polarity. Rab11a affected the distribution of polarity proteins in the vestibular organs, indicating that the normal development of cilia requires Rab11a and intraflagellar transportation. Furthermore, small G protein migration works together with intraflagellar transportation in the normal development of cilia.